2005
DOI: 10.1063/1.1920350
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the wind in Rayleigh–Bénard convection

Abstract: Using a symmetry-accounting ensemble-averaging method, we have identified the wind in unbounded Rayleigh-Bénard convection. This makes it possible to distinguish the wind from fluctuations and to identify dynamic features of each. We present some results from processing five independent three-dimensional direct numerical simulations of a ⌫ = 4 aspect-ratio domain with periodic side boundaries at Ra=10 7 and Pr= 1. It is found that the wind boundary layer scales linearly very close to the wall and has a logarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…An interesting issue concerns the possible presence of energy in the Krishnamurti-Howard flow at k = 0, which is allowed by periodic boundary conditions. In our previous work [21], as in Hartlep et al [20,22] and van Reeuwijk et al [23], we found no evidence for the excitation of the k = 0 mode. The same is observed here, even with much larger values of the aspect ratio.…”
Section: The Saturation Scalesupporting
confidence: 48%
See 1 more Smart Citation
“…An interesting issue concerns the possible presence of energy in the Krishnamurti-Howard flow at k = 0, which is allowed by periodic boundary conditions. In our previous work [21], as in Hartlep et al [20,22] and van Reeuwijk et al [23], we found no evidence for the excitation of the k = 0 mode. The same is observed here, even with much larger values of the aspect ratio.…”
Section: The Saturation Scalesupporting
confidence: 48%
“…These structures have approximately circular horizontal cross-sections with diameters comparable to the boundary layer thickness and they typically traverse the full body of the fluid [1,2]. When the aspect ratio of the container is moderately large (horizontal domain size of about 4 to 6 times the layer depth) the plumes are found to congregate into patterns associated with large-scale circulations that have been studied experimentally [3][4][5][6][7][8][9][10], analytically [11][12][13][14] and numerically [15][16][17][18][19][20][21][22][23]. The dependence of the properties of turbulent convection and of large-scale circulations on aspect * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that both the Kolmogorov and Yaglom equations are satisfied is also evidence of the fact that the terms associated with the possible presence of a mean flow are negligible. Indeed, it should be pointed out that a mean velocity field would exist locally in time and space due to the presence of large-scale circulations which erratically reverse their directions on time scales exceeding the large eddy turnover time as reported in Van Reeuwijk, Jonker & Hanjalić (2005), Brown & Ahlers (2006) and Xi, Zhou & Xia (2006). It is well known that by increasing the Rayleigh number the characteristic length scales of the problem decrease.…”
Section: A)mentioning
confidence: 97%
“…There is an inhomogeneous flow structure that causes the discrepancy: just as in Rayleigh-Bénard convection in cylindrical domains, convection in a horizontally periodic domain is known to organize into a domain-filling circulation pattern, e.g., Refs. [42,45,46]. This circulation forms with a random orientation and then changes its orientation only very slowly.…”
Section: Scale-by-scale Energy Budgetmentioning
confidence: 99%